Selection of Commercially Available Membrane between Resorbable and Nonresorbable Materials for Guided Bone Regeneration - Rakhmatia, Yunia Dwi; Ayukawa, Yasunori; Furuhashi, Akihiro; Koyano, Kiyoshi (Journal of Dentistry Indonesia, 2022)
Objective: This study aims to evaluate the commercially available membranes used for treatment in Guided Bone Regeneration (GBR). Methods: Four membranes resorbable and non-resorbable were used and a critical size defect in six-week-old Wistar rats was created for membrane application. Meanwhile, the defect without membrane treatment was used as the control (C). Results: After 4 and 8 weeks, all rats were euthanized and block biopsies of calvaria including membrane were excised and analysed using microcomputed tomography (micro-CT). The sections were dehydrated with graded ethanol, embedded in resin, and cut for histologic evaluation. After 4 weeks, all membrane groups and the control showed different degrees of bone volume (BV) and mineral density (BMD). Titanium mesh (TM) was observed with higher bone volume but lower BMD compared to the control, Cytoplast (CP), Biomend (BM), and GC membranes. The results showed that newly formed bone adjacent to the original filled the defect area. Conclusion: TM was the stiffest among the commercially available membranes used and increased the abundance of bone formation at 4 weeks. The selection of membranes used in GBR needs to consider the treatment requirement and the patient’s point of view.